Artificial gametes, the unnatural and the artefactual. Issue 6 (5th March 2018) - Smajdor, Anna; Cutas, Daniela; Takala, Tuija
Abstract : In debates on the ethics of artificial gametes, concepts of naturalness have been used in a number of different ways. Some have argued that the unnaturalness of artificial gametes means that it is unacceptable to use them in fertility treatments. Others have suggested that artificial gametes are no less natural than many other tissues or processes in common medical use. We suggest that establishing the naturalness or unnaturalness of artificial gametes is unlikely to provide easy answers as to the acceptability of using them in fertility medicine. However, we also suggest that we should be cautious about repudiating any relationship between nature and moral evaluation. The property of being natural or man-made may not per se tell us anything about an entity's moral status, but it has an important impact on the moral relationship between the creator and the created organism.